Glucocorticoids Misuse among Premenopausal Women in Southern Iraq (Journal of Pharmaceutical Negative Results, 2022)
Background: The non-prescription usage of these medications is high because of their spectacular response and various available formulations, despite the fact that they have several negative effects.GCs misuse is an important problem that has been inadequately addressed in Iraq. The purpose of female misuse of GCs is to become beautiful, plump, and seductive (fat body, which is culturally acceptable in some communities) through weight gain or marriage. The objectives of the study were to evaluate the causes of GCs misuse among reproductive women in the South of Iraq.Methods: a cross-sectional study was conducted on 251 reproductive-aged women who were misusing GCs for any cause and attending Thi-Qar Specialized Diabetes, Endocrine and Metabolism Center (TDEMC). They were evaluated for demographic characteristics, medical and social histories, and then examined carefully for any signs of GCs misuse.Results: The mean ages of women were 33.21±8.6 years, BMI 30.68±7.3 Kg/m², and 208 (82.9%) women were either overweight or obese. The 251 subjects misuse glucocorticoids most were married: 195 (77.7%); of medium social class: 142 (56.6%); lived in the city center: 198 (78.9%).Two hundred and one (80.1%) patients obtained the drug from the pharmacy and 18 (7.2%) from street vendors.Nearly all women had many features of GCs-induced adverse effects, weight gain was the highest side effect in 234 (93.2%) patients, and there were many misconceptions about their safety as 41.8% thought that using GCs was safe, and 45.8% did not feel guilty about using those medications.About 90 of them (35.9%) were still misusing drugs during the time of the meeting, 53 (21.1%) reported that physicians recommended them at the first time for using glucocorticoids and the majority 198 (78.9%) were misusing GCs by themselves, friends, or first-degree family to become beautiful or marry.Conclusions: This study showed high misuse of GCs among females in The-Qar, Iraq. The relatively high rate of misuse of these drugs can be attributed to a lack of awareness of their chronic adverse effects, their widespread availability at pharmacies, plus their dramatic and quick response. Therefore, educational programs have to be implemented to inform the public about the adverse effects of GCs and the problems of misuse of drugs.